Hormone Replacement Therapy (HRT) and its correlation with endometrial cancer in climacteric women: A systematic review - da Silva Oliveira, Marilia Rebeca; Postorivo Nauman, José Vicente (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Background: During the climacteric, the female body suffers from a decrease in ovarian activity with a reduction in circulating estrogen levels and consequently signs and symptoms appear such as infertility, vasomotor disorders, atrophy of the genitalia and, in the long term, increased bone turnover, cardiovascular diseases, alterations of the lipid profile among others that interfere with the quality of life. Hormone replacement therapy (unopposed estrogens or associated with progestins) is used as part of the treatment to suppress these symptoms, but it is associated with the risk of developing endometrial cancer, which is hormone dependent. Material and methods: A systematic search of the best available evidence is carried out in information sources and databases, such as PubMed, Cochrane, Epistemonikos, Societies (SEGO, NCCN, FIGO, ESMO-ESGO-ESTRO) in search of studies that correlate HRT as a risk factor for developing endometrial cancer. Results: the evidence showed that estrogen HRT in isolation considerably improves symptoms in women, but that it substantially increases the risk of developing endometrial cancer because it is hormone dependent. Conclusion: It is necessary to understand the use of HRT, be it unopposed estrogens or associated with progestogens, in the climacteric, to whom it can be indicated and how to implement it to improve the quality of life of these women